Numerical Simulation Study on the Influence of Roof-Cutting Angle on the Stability of Gob-Side Entry Retaining Without Coal Pillars - Zhang, Yi (International Journal of Natural Resources and Environmental Studies, 2025)
For the gob-side entry retaining of the 21311 auxiliary intake airway in Xiangshan Mine, a numerical calculation model for automatic entry formation through roof cutting and pressure relief in the fully-mechanized mining face of Xiangshan Mine was established using numerical simulation software. The model simulated the stress and displacement distribution characteristics of the surrounding rock when the roof-cutting height was 6 m and the slit angles were 0°, 5°, 10° and 15°. It also analyzed the impact of the roof-cutting angle on the pressure relief effect. The research results indicate that increasing the roof-cutting angle is conducive to pressure relief on the roadway roof, but the effect becomes less pronounced once the angle increases to a certain extent. Through numerical simulation, it was determined that when the reasonable roof-cutting height in Xiangshan Mine is 6 m, the reasonable roof-cutting angle is 10°.